Takedown : a thriller - Thor, Brad (New York : Atria Books, 2006)
Former Navy SEAL and covert counter-terrorism agent Scot Harvath is sent to the streets of Manhattan after a deadly terrorist attack to find a man so powerful the government will do anything to keep him hidden.
Keywords: Intelligence officers -- United States -- Fiction; Detective and mystery fiction